Collecting system invasion and Fuhrman grade but not tumor size facilitate prognostic stratification of patients with pT2 renal cell carcinoma - Brookman‐May, Sabine D.; May, M.; Zigeuner, R.; Shariat, S. F.; Scherr, D. S.; Chromecki, T.; Moch, H.; Wild, P. J.; Mohamad, -Al-Ali B.; Cindolo, L.; Wieland, W. F.; Schips, L.; et al. (The journal of urology, 2011)
Purpose: - - The 7th edition of TNM for renal cell carcinoma introduced a subdivision of pT2 tumors at a 10 cm cutoff. In the present multicenter study the influence of tumor size as well as further clinical and histopathological parameters on cancer specific survival in patients with pT2 tumors was evaluated. - - Materials and Methods: - - A total of 670 consecutive patients with pT2 tumors (10.4%) of 6,442 surgically treated patients with all tumor stages were pooled (mean followup 71.4 months). Tumors were reclassified according to the current TNM classification, and subdivided in stages pT2a and pT2b. Cancer specific survival was analyzed using the Kaplan-Meier method, and univariable and multivariable analyses were used to assess the influence of several parameters on survival. - - Results: - - Tumor size continuously applied and subdivided at 10 cm or alternative cutoffs did not significantly influence cancer specific survival. In addition to N/M stage, Fuhrman grade and collecting system invasion also had an independent influence on survival. Integration of a dichotomous variable subsuming Fuhrman grade and collecting system invasion (grade 3/4 and/or collecting system invasion present vs grade 1/2 and collecting system invasion absent) into multivariate models including established prognostic parameters resulted in improvement of predictive abilities by 11% (HR 2.3, p <0.001) for all pT2 cases and 151% (HR 3.1, p <0.001) for stage pT2N0M0 cases. - - Conclusions: - - Tumor size did not have a significant influence on cancer specific survival in pT2 tumors, neither continuously applied nor based on various cutoff values. To enhance prognostic discrimination, multifactorial staging systems including pathological features should be implemented. The prognostic relevance of the variable subsuming Fuhrman grade and collecting system invasion should be considered for future evaluation.
Gesehen am 23.06.2022